Implikasi Trend Wisata Alternatif Terhadap Sosial Ekonomi Masyarakat Di Desa Wisata Tista, Kabupaten Tabanan - Bastiyan, Yudi; Bhaskara, Gde Indra; Sastrawan, I Gede Anom (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i01.p01, 2024)
A tourism village is one of the alternative tourism forms that is widely developed in Indonesia nowadays. The popularity of alternative tourism and the development of tourism villages make it crucial to learn about its socioeconomic implications for the local community. The tourism village of Tista is situated in Kerambitan, Tabanan Regency. Tista Tourism Village contents of various natural, cultural, spiritual, and culinary potentials that are turned into its tourism products. This study aimed to discover the implications of alternative tourism trendstowards the socioeconomic life of the locals in the tourism village of Tista. This study is conducted using qualitative and quantitative data. Data resources are primary and secondary data. Data collection used are interviews, observation, documentary study, and documentation. Data analysis stages include data collection, data reduction, data display, and conclusion drawing/verification The results indicate that alternative tourism trend and the widespread development of tourism villages caused several implications for the locals including opportunities to work and have culinary and souvenir businesses, while some locals are still maintaining their profession mainly as farmers and do not proceed to the tourism field. Social implication happens such as the escalation of the local community’s welfare, nevertheless, it emerges the violation of certain rules in the society. Keywords: Tourism Impacts, Alternative Tourism, Socio-Economic, Tista Tourism Village